Hubungan Keterlibatan Dan Konsistensi Dengan Produktivitas Kerja Perawat Di RSUD I Lagaligo Wotu - Anas Budi; Armawati Abidin (HEALTH CARE : JURNAL KESEHATAN, 2020)
The organizational culture has a strong influence throughout the hospital, apart from being an identity, it is also a reference or guide for nurses’ behavior. The relationship between organizational culture and work productivity of nurses has a positive impact on the hospital, where organizational culture can lead nurses to be productive. This study aimed to find out the extent of involvement and consistency with the work productivity of nurses in Lagaligo Wotu Regional Hospital, East Luwu Regency. This study was a quantitative research with a correlation descriptive research design. The research subjects were 81 nurses in the inpatient room of I Lagaligo East Luwu Regional Hospital. The measuring instrument used was a questionnaire. The results of bivariate analysis using the Spearman Correlation test showed that there was a positive and significant relationship between work involvement and productivity with a value of p = 0.001, and there was a positive and significant relationship between consistency and work productivity. with p value = 0.001.